2010
DOI: 10.1007/s00464-010-0900-x
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic colectomy is safe and leads to a significantly shorter hospital stay for octogenarians

Abstract: Complications and other outcomes are similar for LC and OC, and the earlier recovery associated with LC, as evidenced by a shorter hospital stay, may encourage a wider adoption of LC for patients older than 80 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 23 publications
(29 reference statements)
4
28
0
1
Order By: Relevance
“…In our study, 7.8% of patients suffered cardio-respiratory complications. This is comparable to rates of 6.7% to 14.4% quoted in the literature [6,11,13,28]. Of note, incidence of cardio-respiratory complications was similar in both LC and OC groups but mortality rate from these complications was higher in the OC group.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, 7.8% of patients suffered cardio-respiratory complications. This is comparable to rates of 6.7% to 14.4% quoted in the literature [6,11,13,28]. Of note, incidence of cardio-respiratory complications was similar in both LC and OC groups but mortality rate from these complications was higher in the OC group.…”
Section: Discussionsupporting
confidence: 90%
“…Perioperative outcomes in laparoscopic surgery for the elderly remain non-conclusive. In laparoscopic colectomies, postoperative outcomes were noted to be similar in both elderly and younger patients in some studies [6][7][8], while others, however, have shown superior outcomes in the LC group [9][10][11][12][13][14][15]. Studies examining laparoscopic surgery in both young and elderly patients have found that the benefits of laparoscopic surgery are more marked in elderly patients [16,17].…”
Section: Introductionmentioning
confidence: 91%
“…Following analysis, LC was found to be associated with a significantly lower estimated blood loss and intraoperative transfusion rate, although the operative time was longer when compared to laparotomy. These results are similar to those reported by previous studies, as the operative time of the laparoscopic procedure was reported to be 20-30 min longer compared to laparotomy (9)(10)(11)(12). Only in the study by Senagore et al was the operative time reported to be shorter with LC (14), but no further discussion was offered regarding this finding.…”
Section: Discussionsupporting
confidence: 73%
“…The decreased hospital stay reflects the faster postoperative recovery of oral intake of food, bowel function and physical activity (9,10,(15)(16)(17)(18), athough such variables were not analyzed in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation